THE CONCEPT OF COUNTRY AND LEADERSHIP IN ISLAMIC POLITICAL PHILOSOPHY OF IBN TAIMIYAH - Matroni ,; Moh Ikmal; Hasan Basri (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2022)
The concept of the caliphate as a discourse and promoted by several groups of Islamic fundamentalist movements, is no longer able to fulfill the goals of government in Islam. Ibn Taimiyah finally promised an Islamic political theory which was expected to be able to cover the shortcomings and limitations of the khilafah theory by referring to the classical caliphate theory. Ibn Taimiyah's political theory is contained in one of his works entitled al-Siyasah al-Syar'iyah fi islah al-Ra'i wa al- Ra'iah (Shari'ah-based Politics for the Improvement of Returners and Shepherds). Departing from the basis of the classical theory of caliphate,he not only criticized the caliphate theory, but at the same time saw that there was no need for a caliphate. Even Ibn Taimiyah argues that in the Koran and as-Sunnah does not formulate a caliphate. The existence of the historical background of the Khilafah Khilafah al-Rasyidin is nothing more than an accident, not an example of political life. Even the life of the Prophet is not seen as the basis of government that needs to be adopted in a particular political system of government, he is nothing but a suigeneris institution, not the basis of Islamic politics. Ibn Taimiyah's rejection of the practice of history as the basis of political philosophy,then Ibn Taimiyah avoided the error of assessing the existing political power as power legalized by the shadow of the caliph, as contained in the characteristics of the political theory of previous thought.